Strategic marketing in tourism services - Tsiotsu, Rodoula H.; Goldsmith, Ronald E. (Emerald Group Publishing Limited, 2012)
Tourism services all over the world currently face rapid changes due to market globalization, intensified competition and the dynamic evolution of new technologies. Moreover, it is expected that tourism will be one of the industries that will be most affected by the current recession. The long-term success of tourism services in such a fierce competitive and financially difficult environment depends not only on being able to satisfy customers' needs and desires, but to strategically respond to current global challenges. Therefore, strategic marketing becomes a necessary practice in contemporary tourism services firms. Strategic Marketing in Tourism Services focuses on marketing strategies implemented in tourism services firms and includes a collection of papers related to specific marketing strategies. The book presents the application of specific marketing strategies such as experiential marketing, branding, target marketing, relationship marketing and e-marketing in tourism. Furthermore, it presents the strategic responses of each tourism sub-sector - hospitality, air transport, tour operation, travel agencies and the tourism destinations - from various countries around the world.